Impact of the COVID-19 Pandemic and Vaccine Availability on Utilization of Breast Imaging in a Multistate Radiology Practice - Andrew K. Hillman; Phil Ramis; Patrick Nielsen; Eric M. Rohren (Radiology Research and Practice)
Purpose of Study. Our study evaluated the impact of COVID-19 on breast imaging volumes and the recovery of these volumes following availability of COVID-19 vaccination. Method. Data were obtained from medical health records across 77 Radiology Partners practices in the US. The data provided us with the total monthly mammography, breast ultrasound, and breast MRI procedures from January 2019 to September 2022. An interrupted time-series (ITS) analysis was conducted to evaluate the effect of the COVID-19 pandemic and the COVID-19 vaccination. We chose March 2020 and December 2020 as critical time points in the pandemic and analyzed trends before and after these dates. Results. The starting level (at baseline in January 2019) of the total breast imaging procedure volume was estimated at 114,901.5, and this volume appeared to significantly increase every month prior to March 2020 by 4,864.0 (p<0.0001, CI = [3,077.1, 6,650.9]). In March 2020, there appeared to be a significant decrease in volume by 104,446.3 (p=0.003, CI = [−172,063.1, −36,829.5]), followed by a significant increase in the monthly trend of service volume (relative to the pre-COVID trend) of 20,660.7 per month (p=0.001, CI = [8,828.5, 32,493.0]). In December 2020, there appeared to be a significant decrease in service volume by 69,791.2 (p=0.012, CI = [−123,602.6, −15,979.7]). Compared to the period from March to November 2020, there was a decrease in the monthly trend of service volumes per month by 24,213.9 (p<0.0001, CI = [−36,027.6, −12,400.2]). After March 2020, the total service volume increased at the rate of 25,524.7 per month (p<0.0001, CI = [13,828.2, 37,221.2]). In contrast, the service volumes after December 2020 appeared to grow steadily and slowly at a rate of 1,310.8 per month (p=0.118, CI = [−348.8, 2970.3]). Conclusion. Our study revealed that there has been a recovery and a further increase in breast imaging service volumes compared to prepandemic levels. The increase can be best explained by vaccination rollout, reopening of elective/nonemergency healthcare services, insurance coverage expansion, the decline in the US uninsured rate due to government interventions and policies, and the recovery of jobs with employer-provided medical insurance post-pandemic.